Pharmacological activation of AMPK prevents Drp1-mediated mitochondrial fission and alleviates endoplasmic reticulum stress-associated endothelial dysfunction. (September 2015) - Li, Jia; Wang, Yilei; Wang, Yapu; Wen, Xiaodong; Ma, Xiao-Nan; Chen, Weijie; Huang, Fang; Kou, Junping; Qi, Lian-Wen; Liu, Baolin; Liu, Kang
Abstract: Background and purpose: This study aims to investigate whether and how pharmacological activation of AMP-activated protein kinase (AMPK) improves endothelial function by suppressing mitochondrial ROS-associated endoplasmic reticulum stress (ER stress) in the endothelium. Experimental approach Palmitate stimulation induced mitochondrial fission and ER stress-associated endothelial dysfunction. The effects of AMPK activators salicylate and AICA riboside (AICAR) on mitochondrial ROS production, Drp1 phosphorylation, mitochondrial fission, ER stress, thioredoxin-interacting protein (TXNIP)/NLRP3 inflammasome activation, inflammation, cell apoptosis and endothelium-dependent vasodilation were observed. Key results "Silencing" of TXNIP by RNA interference inhibited NLRP3 inflammasome activation in response to ER stress, indicating that TXNIP was a key link between ER stress and NLRP3 inflammasome activation. AMPK activators salicylate and AICAR prevented ROS-induced mitochondrial fission by enhancing dynamin-related protein 1 (Drp1) phosphorylation (Ser 637) and thereby attenuated IRE-1α and PERK phosphorylation, but their actions were blocked by knockdown of AMPK. Salicylate and AICAR reduced TXNIP induction and inhibited NLRP3 inflammasome activation by reducing NLRP3 and caspase-1 expression, leading to a reduction in IL-1β secretion. As a result, salicylate and AICAR inhibited inflammation and reduced cell apoptosis. Meanwhile, salicylate and AICAR enhanced eNOS phosphorylation and restored the loss of endothelium-dependent vasodilation in the rat aorta. Immunohistochemistry staining showed that AMPK activation inhibited ER stress and NLRP3 inflammasome activation in the vascular endothelium. Conclusion and implications: Pharmacological activation of AMPK regulated mitochondrial morphology and ameliorated endothelial dysfunction by suppression of mitochondrial ROS-associated ER stress and subsequent TXNIP/NLRP3 inflammasome activation. These findings suggested that regulation of Drp1 phosphorylation by AMPK activation contributed to suppression of ER stress and thus presented a potential therapeutic strategy for AMPK activation in the regulation of endothelium homeostasis. Highlights: AMPK inhibits ROS-ER stress and TXNIP/NLRP3 inflammasome activation in endothelium. TXNIP induction is essential for ER stress-induced NLRP3 activation in endothelium. AMPK prevents mitochondrial fission and ER stress by upregulating p-Drp1 (S637).